Treatment of a horizontally impacted permanent incisor in a 9-year-old girl: A Case Report - Shekarian, Shiva; Behnaz, Mohammad (Journal of Dental School, 2019)
Impaction of maxillary central incisors is not common. Treatment of an impacted central incisor is challenging as it relates to facial esthetics and dental function. Although impaction of permanent teeth is rarely diagnosed in mixed dentition period, an impacted central incisor is usually diagnosed when there is a delay in the eruption of tooth. Tooth impaction may result from a number of local etiological factors such as lack of space for eruption, presence of supernumerary teeth, disturbances in the path of eruption and presence of pathological cysts. Management options for such teeth include (1) surgical extraction and moving the lateral incisor to replace the central incisor and changing the anatomy of other teeth, (2) extraction of the impacted tooth followed by bridge or implant placement, (3) surgical repositioning of the impacted tooth, and (4) orthodontic correction of the impacted tooth. The purpose of this article was to describe surgical exposure and orthodontic treatment of a horizontally impacted permanent maxillary central incisor, parallel to the occlusal plane in a 9-year-old girl. The impacted tooth was surgically exposed and traction was done with orthodontic intervention.